Chlorination of poly(vinyl chloride) model compounds in radical‐complexing solvents. Issue 4 (28th January 2015) - Ge, Xianlong; Starnes, William H.
Abstract : A potential route to the preparation of poly(1, 2‐dichloroethylene) by the selective chlorination of poly(vinyl chloride) (PVC) was explored. During free‐radical chlorinations with Cl2, certain solvents play the very important role of forming complexes with the free chlorine atom that lead to changes in the pattern of chlorine substitution. In our work, the photochlorination of three model compounds for PVC, namely, 2, 4‐dichloropentane, 3‐chloropentane, and 4‐chloroheptane, was carried out with molecular chlorine in the absence or presence of complexing solvents. The effects of these solvents on the chlorination selectivity were determined. During the conventional chlorination of sec‐alkyl chlorides with molecular chlorine, bridged‐radical intermediates are believed to be involved. They lead to vicinal dichlorides as the major products. However, we found that complexing solvents significantly increased the yields of geminal dichlorides instead. Such solvents also are well known to decrease reactivity in free‐radical chlorinations with Cl2 . Thus, for both of these reasons, the chlorination of PVC with Cl2 in complexing solvents is unlikely to be useful for the preparation of poly(1, 2‐dichloroethylene). J. VINYL ADDIT. TECHNOL., 22:405–409, 2016. © 2015 Society of Plastics Engineers